Exploring the effects of elaborated and motivational feedback on learning engagement in online scripted role discussion - Qinna Feng; Wenhao Li; Xueping Zhu; Xiuhan Li (International Journal of Educational Technology in Higher Education)
Abstract Giving feedback is key to online collaborative discussion, but the impact of feedback on role-scripts in online discussion remains unclear. To address this research gap, a mixed factorial experiment was conducted to investigate the potential effects and interactions of feedback type (elaborated vs. motivational feedback) and scripted roles (yes vs. no) on behavioral, cognitive, and emotional engagement. Fifty participants enrolled in an undergraduate blended course were randomly assigned to a role-script group (n = 25) and a role-free group (n = 25). Both groups received elaborated and motivational feedback sequentially. Mixed ANOVA results showed that (a) scripted roles significantly facilitated behavioral engagement; (b) elaborated feedback intrigued more cognitive engagement compared to motivational feedback; (c) the role-scripting strategy and feedback type had an interaction effect on behavioral engagement; and (d) there was a significant difference in cognitive engagement among various roles. The epistemic network analysis results revealed evolving cognitive engagement patterns associated with distinct roles when exposed to two distinct types of feedback. The implications of these findings for the design and implementation of online discussions are discussed.